Promoting rigor in blockchain energy and environmental footprint research: A systematic literature review - Ashish Rajendra Sai; Harald Vranken (Blockchain: Research and Applications, 2024)
There is a growing interest in understanding the energy and environmental footprint of digital currencies, specifically in cryptocurrencies such as Bitcoin and Ethereum. These cryptocurrencies are operated by a geographically distributed network of computing nodes, making it hard to estimate their energy consumption accurately. Existing studies, both in academia and industry, attempt to model cryptocurrency energy consumption often based on a number of assumptions, for instance, about the hardware in use or the geographic distribution of the computing nodes. A number of these studies have already been widely criticized for their design choices and subsequent over- or under-estimation of energy use.In this study, we evaluate the reliability of prior models and estimates by leveraging existing scientific literature from fields cognizant of blockchain, such as social energy sciences and information systems. We first design a quality assessment framework based on existing research, and we then conduct a systematic literature review examining scientific and non-academic literature demonstrating common issues and potential avenues of addressing these issues.Our goal with this article is to advance the field by promoting scientific rigor in studies focusing on blockchain energy footprint. To that end, we provide a novel set of codes of conduct for the five most widely used research methodologies: Quantitative energy modeling, literature reviews, data analysis and statistics, case studies, and experiments. We envision that this code of conduct would assist in standardizing the design and assessment of studies focusing on blockchain-based systems' energy and environmental footprint.